A reference protocol for comparing the biocidal properties of gas plasma generating devices. (5th November 2015) - Shaw, A; Seri, P; Borghi, C A; Shama, G; Iza, F
Abstract: Growing interest in the use of non-thermal, atmospheric pressure gas plasmas for decontamination purposes has resulted in a multiplicity of plasma-generating devices. There is currently no universally approved method of comparing the biocidal performance of such devices and in the work described here spores of the Gram positive bacterium Bacillus subtilis (ATCC 6633) are proposed as a suitable reference biological agent. In order to achieve consistency in the form in which the biological agent in question is presented to the plasma, a polycarbonate membrane loaded with a monolayer of spores is proposed. The advantages of the proposed protocol are evaluated by comparing inactivation tests in which an alternative microorganism (methicillin resistant Staphylococcus aureus —MRSA) and the widely-used sample preparation technique of directly pipetting cell suspensions onto membranes are employed. In all cases, inactivation tests with either UV irradiation or plasma exposure were more reproducible when the proposed protocol was followed.